JAPANESE MULTINATIONAL CORPORATIONS EXPANSION STRATEGY CASE STUDY: HONDA MNC EXPANSION STRATEGY IN INDONESIA - Zaelani, Iwan Ridwan; Sihotang, Eky Rahmadani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan Bandung, 2022)
MNCs in Indonesia seeks to provide an overview of activities in Indonesia. Especially in the automotive sector, Astra Honda Motor, which merged with Astra International. This research uses the strategies used by MNCs to dominate and expand the market.The main objective of MNC is to gain profit, present globalization to be one stepping stone for MNC to achieve the goals. Globalization offers interconnection in various fields and disguises national borders, thus the market will be easier to carry out its economic activities.Indonesia is one of the countries that are friendly to investors, Indonesia has an agreement that gives freedom to multinational coorporation in developing their business in Indonesia.In this discussion, the author discusses the discussion about thinking to analyze research problems, namely the market domination strategy of motorcycle sales carried out by PT. Astra Honda Motor in Indonesia, using descriptive analysis. The basic thinking that is used is trade liberalization to explain market activity which will run better if it does not get more assistance from the state, then globalization which provides convenience in all activities and MNC movements in obtaining goals that are truly by following market developments.The explanation in the discussion has four parts. First, regulations in Indonesia are related to multinational coorporation. Second, bilateral relations between Indonesia and Japan. Third, Characteristics of Japanese multinational coorporation. Fourth, Honda's market dominance strategy.